HIV/AIDS SEBAGAI PROBLEMATIKA DAKWAH Studi Terhadap Implementasi Kebijakan Penanganan - Rasyidah Rasyidah (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2019)
Aceh Utara is a district that provides the most PLWHA data in Aceh. However, with the title "Serambi Mekkah", the handling of PLWHA as a“da’wah bi al hal”, can be difficult. There is a stigma in the community to let PLWHA accept the risk of their actions, so that the da’wah is also considered unnecessary. This study tries to answer the question: what is the policy related to the handling of HIV AIDS, how its implementation, and its effectivness.This qualitative research uses descriptive analysis with data collection techniques: observation, interview and documentation study. The results of the study are: HIV/AIDS policies in North Aceh, merged with national policies on "Prevention of Communicable Diseases". There is no specific policy. It’s to prevent public resistance and causing controversy. There are four strategies in solving HIV/AIDS. First, accurate data collection. Second, through the institution of the AIDS Commission (KPA) which is intense in reaching and assisting PLWHA. Third, improving the quality of life of PLWHA. Fourth, socialization in the community and strengthening the role of assistant through the “Desa Siaga HIV/AIDS”, networking and appreciation for survivors and companions of PLWHA. Although there is a dualism of understanding related to da’wah to PLWHA, but it should be, for the da’wah of community development, PLWHA are mad'u who must be helped to strengthen Islam in their lives. Keywords: HIV, AIDS, PLWHA, Policy